Severe CMV complication following maintenance therapy with rituximab. (9th January 2013) - Le Clech, Lenaïg; Ianotto, Jean-Christophe; Quintin-Roue, Isabelle; Tempescul, Adrian
Abstract : Cytomegalovirus (CMV) encephalitis is a rare infection that immunodeficient patients, mainly where HIV-positive, may suffer from. Several cases were described when complications with the treatment with monoclonal antibodies, like rituximab, for malignant lymphomas. We will describe here the case of a patient, who has developed CMV gastritis, then CMV encephalitis after the treatment of a CLL with a chemotherapy and maintenance therapy with rituximab.